2013
DOI: 10.4103/1755-6783.116508
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Kell blood group in Kashmiri population attending blood bank SKIMS as donors

Abstract: Purpose:To determine anti-Kell in Kashmiri population. Material and Methods: Prospective study of One Year.Result: Six patients were tested positive. Conclusion: The incidence of Kell is very low i.e., 0.03% and correlates to the incidence of Japanese.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…Our results match with those of Shah et al (91.70% vs. 85.18%) and Ashraf et al who also observed K to be significantly frequent among blood group A as compared to B. 11,14 While Rani et al in India observed no marked difference (3.49% vs. 3.23%). 15 To conclude, we observed Kell antigens K and k in 3.6% and 96.3% of blood donors respectively presenting at blood banks of Sheikh Zayed Hospital, Lahore and Jinnah Hospital, Lahore.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our results match with those of Shah et al (91.70% vs. 85.18%) and Ashraf et al who also observed K to be significantly frequent among blood group A as compared to B. 11,14 While Rani et al in India observed no marked difference (3.49% vs. 3.23%). 15 To conclude, we observed Kell antigens K and k in 3.6% and 96.3% of blood donors respectively presenting at blood banks of Sheikh Zayed Hospital, Lahore and Jinnah Hospital, Lahore.…”
Section: Discussionsupporting
confidence: 92%
“…Shah et al in 2013 also observed similar male predominance among blood donors (85% Males; vs. 15% Females) in Kashmir. 11 On the other hand, Mustafa et al in 2014 reported nearly equal proportion of donors from both genders (54% Males vs.46% Females) in Saudi Arabia. 12 This male predominance in our society can be attributable to poor nutritional and health status of women in general along with myths and phobias about the blood donation and educational status of population.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Kell blood group system is the next most clinically significant after the ABO and Rhesus blood group system [ 27 ]. Antibodies to the Kell antigen have been incriminated in HDFN and in haemolytic transfusion reactions [ 28 30 ]. Anti-K typically presents as IgG class alloantibody.…”
Section: Resultsmentioning
confidence: 99%